Pathogen-reduced platelets for the prevention of bleeding (Review) - Estcourt, L; Malouf, R; Hopewell, S; Trivella, M; Doree, C; Stanworth, S; Murphy, M (Wiley, 2017)
Review question The aim of this review was to assess whether specially treated pathogen-reduced platelets, work as well as normal platelets when transfused. Specifically, do they stop or prevent bleeding as well as standard platelets; do they produce the same increase in platelet count; and does their use affect further transfusion requirements? This review also assessed whether pathogen-reduced platelets are as safe as normal platelets, for example are they associated with any difference in the rate of death following transfusion, and are there any side effects associated with the use of these products. Our target population was people of any age with a low platelet count who would usually be treated with platelet transfusions. Background Blood for transfusion is collected from donors and then processed and stored as bags of different blood components. One of these components is platelets. Platelets are cells that help the body to form clots and prevent bleeding. Platelet transfusions may be given to prevent bleeding when the platelet count falls below a prespecified threshold platelet count (e.g. 10 x 109/L), or may be given to treat bleeding (such as a prolonged nosebleed or multiple bruises). As for all transfusions, there are risks related to giving platelets transfusions, including a small risk of transfusion-transmitted infections. A number of methods are used to minimise the risk of transfusion-transmitted infections, including careful selection of people who donate blood and rigorous testing of the donated blood. One method of preventing infection is pathogen reduction by which, through a process of adding chemicals to the donated platelets and exposing them to a wavelength of ultraviolet light, the number of infecting organisms can be reduced.We have included two types of pathogen-reduction technique in this review, Intercept® and Mirasol®. Study characteristics The evidence is current to October 2016.We found five new studies eligible for inclusion in this update of the review, three of which are still ongoing. We included 12 randomised controlled trials in this review; in 10 trials the Intercept®method of pathogen-reduction was compared with standard platelets and in two trials theMirasol® method of pathogen-reduction was compared with standard platelets. All trials were conducted between 2003 and 2016 and included a total of 2075 participants. The sources of funding were reported in 12 studies. Most of the included studies were conducted in adults with blood cancers. Key results In people with cancer who have a low platelet count due to their disease or its treatment, we found that pathogen-reduced platelet transfusions lead to an increase in the number of platelet transfusions required and an increase in the risk of no longer achieving a rise in the platelet count after a transfusion (platelet refractoriness). Pathogen-reduced platelet transfusions probably do not affect the risk of death, bleeding, or a serious side effect. None of the studies reported on quality of life. No bacterial transfusion-transmitted infections occurred in the six trials that reported this outcome. There was insufficient evidence for people with other diagnoses. All three ongoing studies are in adults with blood disorders (planned recruitment 1375 participants), there are no ongoing studies in children or in adults with other diagnoses. Findings from this review were based on 12 studies and the 1981 participants who received a platelet transfusion. We did not evaluate any economic outcomes. Quality of the evidence The overall quality of the evidence was low to high, as the estimates were imprecise (risk of death or a serious side effect), and there were differences in estimates for the risk of bleeding between studies.